Mudanças nas práticas pedagógicas do professor: criando um ambiente construcionista contextualizado e significativo para crianças com necessidades especiais físicas - Schlunzen, Elisa Tomoe Moriya (2000)
This research presents the creation of a Significative and Contextualized Constructionist Environment based on the use of the new technologies to improve the teaching-learning process of physically handicapped children. This research includes the elaboration and consolidation of a methodological approach to be used with these children. This methodology was elaborated jointly with three teachers and with the computer science and pedagogic coordinators of the Associação de Assistência à Criança Deficiente - A.A.C.D.. In accordance with this methodology, the teacher uses the computer to value the student's productions in order to support knowledge construction, mediate the formalization of the curriculum concepts, create opportunities for student expression and to evaluate the students based upon their knowledge construction, their self perception and upon the statements of involved individuals. However, it was necessary to review the teacher's pedagogic practices and, consequently, his/her orientation. Consequently, the continuous in-service training sought to encourage the teacher's autonomy, to become self reflective, and to investigate his/her own actions. The new pedagogic practice was based upon the development of projects, allowing the students to solve important issues, generating their need and desire for learning. In this way, learning emerged from the student's interest and context by which the concepts were brought to life, formalized and learned in a global way, creating challenging learning situations, assisting the individual special needs. The results showed that the new learning environment supported a more pleasurable form of teaching, making learning more significant, contemplating the curriculum in a new way, supporting evaluation of the child's development, integrating and contextualizing concepts, valuing the potential and abilities of the special student. Finally, the children were able to discover themselves and to effect their environment, demonstrating cognitive, social, ethical, affective and emotional improvement, in an effort to define him/herself as a being in his totality